Literatur Review: Pengaruh Diet Bebas Gluten (Gluten Free) terhadap Perkembangan Anak Penderita Autis - Awaludin, Triyono Saputra; Hanifah Setiowati; Teguh Wibowo (Jurnal Sains & Kesehatan, 2025)
Autism is a neurological developmental disorder that affects communication, social interaction, and behavior in children. One of the therapies used to reduce autism symptoms is the Casein-Free Gluten-Free (CFGF) diet. This therapy aims to address metabolic disorders caused by the "leaky gut" syndrome, in which gluten and casein are not fully digested, resulting in opioid peptides that can affect brain function. This study focuses on the effectiveness of the CFGF diet in reducing autism symptoms, including improvements in communication skills, emotional responses, and cognitive function. According to previous studies, implementing the CFGF diet is reported to reduce autism symptoms by 60-70%. The implementation of this diet involves replacing foods containing gluten and casein, such as bread and cow's milk, with alternatives like rice flour and almond milk. Adopting the CFGF diet can reduce gut permeability and improve neurological function in individuals with autism. Additionally, this diet is also associated with improved sleep patterns and increased attention in children with autism, which in turn can enhance learning abilities. Nevertheless, the diet must be supervised to ensure that nutritional needs are met. Literature reviews indicate that the CFGF diet has a significant positive impact on reducing autism symptoms, including improvements in eye contact, social behavior, and engagement in group activities. Thus, the CFGF diet can be an effective alternative therapy to support the development of children with autism, especially in social, cognitive, and emotional aspects.